A short introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2011)
For us in the editorial board this is a very special event - the appearance of the first issue of our new journal. Things have moved quite fast for us towards the realization of this project. We met for the first time in December 2009, and now the journal is a reality! The vision, scope and plans of the journal will not be presented here. They are to be found at our homepage: www.nordicwl.dk. If you haven’t done it yet we will strongly recommend you to subscribe to the newsletter of this journal. We also recommend you to sign up for the established community of debate related to the journal and participate in the development of the journal. We are very grateful for the many, high quality papers we already have had submitted to us. For this first issue we have selected papers that together illustrate the diversity in working life research both in topics and in methods. That we are able to do this confirms that our ambition to make a journal that is relevant both for researchers and ‘professional practitioners’ in the development of working life is realistic and should have wide appeal (...)